1991
DOI: 10.1002/poc.610040107
|View full text |Cite
|
Sign up to set email alerts
|

1,5‐Sigmatropic shifts of bromine over a cyclopentadiene ring

Abstract: The intrinsic mechanism of circumambulatory rearrangements of 5‐bromo‐5‐methyl‐1,2,3,4‐tetramethoxycarbonylcyclopentadiene, 5‐bromo‐1,2,3,4 5‐pentamethoxycarbonylcyclopentadien and 5‐bromo‐ 1,2,3,4,5‐pentaphenylcyclopentadiene due to sigmatropic shifts of bromine over the cyclopentadiene ring was proved, using the dynamic 13C and 1H NMR technique, to be governed by successive intramolecular 1,5‐sigmatropic shifts. Semi‐empirical AM1 and MINDO/3 calculations of reactions paths performed for fluoro‐, chloro‐ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…An analysis [98] of the results of a number of other nonempirical and semiempirical calculations on ion adducts in the reactions of electrophilic aromatic substitution (X = H, F, CH 3 ) has led to the conclusion that generally the symmetric type XL VIII structures of n-complexes are not stable. This conclusion has been supported by semiempirical and ab initio calculations of the mechanisms governing the gas-phase reactions of nitrosation [137,138] and nitration [139][140][141] of benzene.…”
Section: Aromatic Electrophilic Substitution Reactionsmentioning
confidence: 75%
See 2 more Smart Citations
“…An analysis [98] of the results of a number of other nonempirical and semiempirical calculations on ion adducts in the reactions of electrophilic aromatic substitution (X = H, F, CH 3 ) has led to the conclusion that generally the symmetric type XL VIII structures of n-complexes are not stable. This conclusion has been supported by semiempirical and ab initio calculations of the mechanisms governing the gas-phase reactions of nitrosation [137,138] and nitration [139][140][141] of benzene.…”
Section: Aromatic Electrophilic Substitution Reactionsmentioning
confidence: 75%
“…The MINDO/3 calculations [137] are in accord with basic outline of the proposed scheme showing at the same time that the conventional views on the structure of the n-complexes as the high-symmetry systems should be modified. The structure XLIX corresponds, similarly to XLVIII, to a point at the top of a flat hill on the PES of C6H6NO +.…”
Section: Aromatic Electrophilic Substitution Reactionsmentioning
confidence: 76%
See 1 more Smart Citation
“…Cyclopentadiene is a nonbenzenoid aromatic compound with a ring system that is smaller than the benzene ring. The reaction pathways for the 1,5-sigma tropic displacement of the nitroso group along the perimeter of 5-nitroso-1,3-cyclopentadiene and its valence isomerization were studied by Minkin et al [5], using a semiempirical MINDO/3 method. Since this molecule has more than one conformer, the quantum chemical calculations and the conformational analysis of the nitroso compounds are more interesting and a useful exercise for theoretical chemists.…”
mentioning
confidence: 99%
“…Since this molecule has more than one conformer, the quantum chemical calculations and the conformational analysis of the nitroso compounds are more interesting and a useful exercise for theoretical chemists. Calculations have been carried out by Minkin et al [5] using the MINDO/3 [6] and UMINDO/3 [7] schemes, respectively, revealed three stable valence isomers corresponding to the PES minimum for 5-nitroso-1,3-cyclopentadiene, which includes pyridine-N-oxide, bicyclo-laza-7-oxa-2,4 heptadiene, and 1,2-oxazepin [5]. Oxazepin has been identified as the most stable valence isomer of 5-nitroso-1,3-cyclopentadiene by MINDO/3 calculations.…”
mentioning
confidence: 99%